STUDI KOMPARATIF POLA PENGELOLAAN SEKOLAH ISLAM BERASRAMA ANTARA SMAIT IHSANUL FIKRI DAN SMAI AL AZHAR - Amin Maghfuri; Suwadi Suwadi (Ta'dib, 2020)
Abstract: In recent years, many Islamic schools have started to innovate by offering a boarding component in their education system. This research intends to examine how the combination of schools and pesantren which is manifested in the form of an Islamic school with boarding system is managed and how the curriculum is implemented in this combination system. This research is a qualitative research that focuses on a comparative study between SMAIT Ihsanul Fikri Boarding School and SMAI Al Azhar Boarding School. The research data were collected using interview, observation and documentation techniques. By using descriptive analysis, the results of this study indicate that 1) The management pattern of islamic school with boarding systems in the two educational institutions shows differences, especially in the structural position of the person in charge of boarding schools as an element of boarding school institutions; 2) Curriculum implementation as a consequence of a combination of two systems in islamic school with boarding system is also different, one of which is more on systemic integration while the other is more on organic integration. Abstrak: Dalam beberapa tahun terakhir, banyak sekolah-sekolah Islam yang mulai berinovasi dengan menawarkan komponen asrama dalam sistem pendidikannya. Penelitian ini hendak mengkaji bagaimana kombinasi sekolah dan pesantren yang termanifestasikan dalam bentuk sekolah berasrasma dikelola serta bagaimana penyelenggaraan kurikulum di dalam sistem kombinasi tersebut. Penelitian ini adalah penelitian kualitatif yang berfokus pada studi komparasi antara SMAIT Ihsanul Fikri Boarding School dan SMAI Al Azhar Boarding School. Data penelitian dikumpulkan dengan teknik wawancara, observasi dan dokumentasi. Dianalisis dengan pendektan analisi deskriptif, hasil penelitian ini menunjukkan bahwa 1) pola pengelolaan kelembagaan sekolah berasrama pada dua lembaga pendidikan tersebut menunjukkan perbedaan, terutama pada posisi struktural penanggung jawab asrama sebagai unsur kelembagaan sekolah berasrama; 2) implementasi kurikulum sebagai konsekuensi kombinasi dua sistem dalam kelembagaan sekolah berasrama juga berbeda, satu diantaranya lebih pada integrasi sistemik sedangkan yang lain lebih pada integrasi organik.